Denda Adat Mengkhitan Anak Perspektif Hukum Islam (Studi di Desa Rambah Kecamatan Tanah Tumbuh Kabupaten Bungo) - Riski Hariyadi; Kholil Syu'aib; Mustiah RH (NALAR FIQH: Jurnal Hukum Islam, 2022)
This study aims to find out specifically the phenomenon of customary fines for children circumcising in Rambah Village, Tanah Tumbuh District, Bungo Regency and review the perspective of Islamic law on this phenomenon. This research is library research and field research, data collection method using interview, observation, and documentation. Data analysis went through three stages, namely data reduction, data presentation, conclusion drawing and verification. This study found that the customary fine practice of circumcising children in Rambah Village occurred because in the process of children circumcising it was considered to have violated twenty laws. Therefore, children circumcision in Rambah Village is subject to sanctions in the form of paying customary fines, the fines are in accordance with applicable customs. In Islam, circumcision is a matter of fitrah, whether male circumcision or female circumcision, there is no argument regarding fines when children circumcising. However, holding walimah circumcision in any form, it is permissible.